2015
DOI: 10.1016/j.sbspro.2015.04.608
|View full text |Cite
|
Sign up to set email alerts
|

Metacognition and Technology Adoption: Exploring Influences

Abstract: As a component of human cognition, executive function is a collection of processes such as attention, planning, and working memory which are related to managing one's cognitive processes and behaviour. Closely aligned with goal setting, the executive function process of metacognition is important for effective learning and, further, relevant to the successful adoption of technologies which are prevalent today. This paper offers an exploration of some of the influences of metacognition on successful technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
(41 reference statements)
1
13
0
2
Order By: Relevance
“…Research is being conducted to look at the effectiveness of the technology and teaching approaches that have been innovated and modified to meet the curriculum needs and to achieve the goal of improving student competency. As the findings of studied by Radovic, Maric & Passey [35], Eyyam & Yaratan [15], Clarebout et al [10], Gurbin [21], Smith, Shin, Kim & Zawodniak [41] and Borba et al [5], have reported that the results of the technology integration and improvement of traditional approach has influenced and had a significant impact on student achievement. According to Mistretta [28], Mat Sina, Talib & Norishaha [26], Brakoniecki, Amador & Glassmeyer [6] and Gurbin [21], most technology products are widely applied and used in learning, such as gadgets like tabs and smartphones, learning aids likes graphic-scientific calculators, web-based, apps, internet-based and more.…”
Section: Introductionmentioning
confidence: 95%
“…Research is being conducted to look at the effectiveness of the technology and teaching approaches that have been innovated and modified to meet the curriculum needs and to achieve the goal of improving student competency. As the findings of studied by Radovic, Maric & Passey [35], Eyyam & Yaratan [15], Clarebout et al [10], Gurbin [21], Smith, Shin, Kim & Zawodniak [41] and Borba et al [5], have reported that the results of the technology integration and improvement of traditional approach has influenced and had a significant impact on student achievement. According to Mistretta [28], Mat Sina, Talib & Norishaha [26], Brakoniecki, Amador & Glassmeyer [6] and Gurbin [21], most technology products are widely applied and used in learning, such as gadgets like tabs and smartphones, learning aids likes graphic-scientific calculators, web-based, apps, internet-based and more.…”
Section: Introductionmentioning
confidence: 95%
“…On the other hand, the increased ability in planning, implementing and evaluating critical analysis of completed tasks made students' confidence to improve. An increase in student confidence is the result of self-support and motivation as they have completed their work on critical analysis well (Alper et al, 2015;Gurbin, 2015;Lukitasari et al, 2014).…”
Section: No Multicollinearity Problemmentioning
confidence: 99%
“…Gurbin [75], in detail, focuses on the issue of linking the diffusion of innovation and metacognition. Referring to [76], he claims that its involvement is important for understanding the complex learning process that facilitates the successful adoption of technology.…”
Section: Metacognition In Mathematics Educationmentioning
confidence: 99%
“…Several authors [81][82][83][84][85] have reported that intervention has resulted in some significant positive changes of participants. Furthermore, metacognition function is developed simultaneously with other competencies [86], so it seems worth investigating the relations of development of metacognition with the development of the effort related to adoption of technologies [75]. As mentioned above, the impact of ICT tools on the school education process is undeniable [19].…”
Section: Metacognition In Mathematics Educationmentioning
confidence: 99%